2007
DOI: 10.1002/jcp.21185
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor substrate (IRS)‐1 regulates murine embryonic stem (mES) cells self‐renewal

Abstract: Mouse embryonic stem (mES) cells are pluripotent cells that can be propagated in vitro with leukemia inhibitory factor (LIF) and serum. Intracellular signaling by LIF is principally mediated by activation of STAT-3, although additional pathways for self-renewal have been described. Here, we identified a novel role for Insulin receptor substrate-1 (IRS-1) as a critical factor in mES cells self-renewal and differentiation. IRS-1 is expressed and tyrosyl phosphorylated during mES cells self-renewal. Differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
1
26
0
1
Order By: Relevance
“…Insulin receptor substrate-1 (IRS-1), which is necessary for BT-IC differentiation, has been shown to be a direct target of miR-145 (Rubin et al, 2007). ER-α is reported to be negatively regulated by miR-145 at two complementary sites, thereby mediating breast cancer cell growth (Spizzo et al, 2010).…”
Section: Mir-145mentioning
confidence: 99%
“…Insulin receptor substrate-1 (IRS-1), which is necessary for BT-IC differentiation, has been shown to be a direct target of miR-145 (Rubin et al, 2007). ER-α is reported to be negatively regulated by miR-145 at two complementary sites, thereby mediating breast cancer cell growth (Spizzo et al, 2010).…”
Section: Mir-145mentioning
confidence: 99%
“…Interestingly, cord levels of IGFs in the newborn are positively associated with the total number of stem cells and with future cancer risk (Savarese et al 2007). In mouse ES cells, the IR/IGF1R substrate IRS1 is a critical component of the self-renewing program (Rubin et al 2007).…”
Section: Ir Expression and Function In Cancer Cellsmentioning
confidence: 99%
“…Shi et al 6 showed that miR-145 inhibits human cancer cell growth in vitro via the 3ЈUTR of the type 1 insulin-like growth factor receptor and its docking protein, the insulin receptor substrate-1 (IRS-1). Rubin et al 80 found IRS-1 was highly expressed in undifferentiated murine embryonic stem cells (mESC), with decreased expression when the cells differentiated. Forced expression of IRS-1 inhibited mESC differentiation suggesting miR-145 and IRS-1 function in stem cell differentiation.…”
Section: Mirs In Human Stem Cell Renewal and Differentiationmentioning
confidence: 99%